Pengaruh Kepercayaan Merek Pada Pembentukan Loyalitas Merek Apple Di Yogyakarta - Rohmad Juari (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
Brands are importance in the consumer market. Brand defined as name, term, sign symbol or design or a combination of them, intended to identify the goods or service of one seller or group of seller and to differentiate them from those competitors. Brands become interface between consumers and the company and consumers may develop loyalty to brands.This study proposes that trust in a brand is important and is key in development of brand loyalty. Trust in a brand is consumer’s willingness to rely on the brand in the face risks, hoping that the brand can give positive results to them. There were three factors hypothesized to influence trust in a brand (Lau and Lee, 1999) include a number of brand characteristics (includes, brand reputation, brand predictability, and brand competence); company characteristics (includes, trust in a company, company reputation, company perceived motives, and company integrity); consumer-brand characteristics (includes, similarity between consumer self concept and brand personality, brand liking, brand experience, brand satisfaction, and peer support).This study used simple regression and multiple regression to analyzed the data. The sample was drawn by a convenience sampling technique. The Sample was 140 passengers of Apple Computer Users were stayed in Yogyakarta. To achieve reliable and valid data we used reliability and construct validity test with confirmatory factor analysis.The results showed that not all of the independent variables from company characteristics, and consumer-brand characteristics have a positive significant effect to trust in a brand however that all of the independent variable from brand characteristics have a significant effect to trust in a brand. The findings reveal that brand characteristics are relatively more important in their effects on consumer’s trust in a brand. The result also showed that trust in a brand is positively related to brand loyalty.